Impact of Knowledge Type and Strategic Orientation on New Product Creativity and Advantage in High‐Technology Firms1. Issue 1 (17th October 2012) - Kim, Namwoon; Im, Subin; Slater, Stanley F.
<x xml:space="preserve">Abstract</x> As different types of knowledge may have different effects on new product positional advantage, knowledge portfolio management in concert with the firm's strategic orientation is indispensable for new product success. However, previous research has not dealt with the knowledge resources and strategic implementations that affect new product development (NPD). To fill in this gap, the current study focuses on two dimensions of knowledge type (knowledge complexity and knowledge tacitness) and two forms of strategic orientation (technological orientation and market orientation), which influence the positional advantages as determinants of NPD outcomes. Drawing on the resource‐based view, this study explains how these knowledge and strategic orientation variables influence new product creativity, which comprised the novel and meaningful characteristics of new products. Finally, it demonstrates how these two dimensions of new product creativity differentially provide product advantages in terms of customer satisfaction and product differentiation, which lead to superior new product performance. A conceptual framework is developed and the related hypotheses provided to incorporate the study variables and to test their relationships in a sample based on data collected from both marketing and project managers from 100 U.S. high‐technology firms. The model estimation results from path analysis demonstrate that reliance on knowledge of high tacitness harms meaningfulness, while reliance on knowledge of high complexity increases both novelty and meaningfulness of new product. As expected, market orientation and technological orientation improve the meaningfulness and novelty dimensions of the new product, respectively. New product novelty and meaningfulness are shown to enhance new product advantage in terms of product differentiation and customer satisfaction, both of which contribute to new product performance. It is also found that the combinative use of market orientation and knowledge complexity, and technological orientation and knowledge tacitness positively influence both the novelty and meaningfulness of new products. This study, using the product‐level analysis, contributes to the literature by clarifying how the firm's different knowledge properties and strategic orientations both play a role as a source of new product creativity, and how new product creativity, as a valuable and rare resource, enhances new product advantage. The study results suggest that project/product managers should increase the transferability and codifiability of unstructured knowledge by stimulating intraorganizational knowledge sharing among NPD team members, and that they should promote both technology and market‐orientated practices to fully develop creativity of new products.